IDENTIFIKASI SISTEM PENGELOLAAN SAMPAH KAWASAN JAKABARING SPORT CITY KOTA PALEMBANG - Ananda, Dwi Aisyah; Muhammad Aminuddin, Kiagus; Usman, Arie Putra (LATERAL: Jurnal Teknik Sipil, 2024)
Palembang City is a metropolitan city with a population of more than 1.5 million, as a result of this, there is a regional expansion, namely in the Jakabaring area where in this area there is Jakabaring Sport City. Jakabaring Sport City is an area that has sports facilities, namely stadiums and other supporting facilities so that it can attract local people to visit if there is a certain event or event. As a result of these results, it can increase waste generation. This study aims to identify the waste management system in the Jakabaring Sport City area of ​​Palembang City. The method used is a survey and observation, namely by measuring the composition of waste. The results of the study showed that the waste collection scheme uses a collection container which will then be transported to a temporary TPS. The results of measuring the composition of waste in this area show that based on the results of the survey on weekdays, namely Monday and Thursday, the largest waste composition was obtained, namely food waste of 36% to 42%, garden waste of 14% to 23% and plastic waste of 17% to 31%. The results of measuring the composition of waste on holidays, namely Sundays, obtained food waste of 36%, plastic waste of 26% and garden/park waste of 14%.